Registration of Barley Varieties in the Czech Republic in 2004. - Vratislav PSOTA (Kvasný průmysl, 2004)
In 2004 the varieties Nitran and Bolina were registered in the Czech Republic. The Slovak variety Nitran has a medium-size grain but yield of sieving fractions over 2.5 mm is low. Grain yield is mean all agricultural production areas. It is a variety with a high content of extract, with a strong activity of proteolytic, amylolytic and cytolytic enzymes. It had clear wort and its composition was on the optimum level.The German variety Bolina is a non-malting variety. It has a medium- size grain, yield of sieving fractions over 2.5 mm is medium too. Grain yield is very high in all agricultural production areas.In 2004 the varieties Nitran and Bolina were registered in the Czech Republic. The Slovak variety Nitran has a medium-size grain but yield of sieving fractions over 2.5 mm is low. Grain yield is mean all agricultural production areas. It is a variety with a high content of extract, with a strong activity of proteolytic, amylolytic and cytolytic enzymes. It had clear wort and its composition was on the optimum level.The German variety Bolina is a non-malting variety. It has a medium- size grain, yield of sieving fractions over 2.5 mm is medium too. Grain yield is very high in all agricultural production areas.